Perception of the media image of health care in society - Jańczyk, Magdalena; Samek, Ilona; Bator, Damian; Dąbrowska, Justyna; Wójcik, Magdalena; Milanowska, Joanna (Journal of Education, Health and Sport, 2020)
Introduction and purpose: The mass media deal with, among others creating the image of health care. Most often, information published in the media is negative because it aims to show sensation and increase the interest of recipients. To present the perception of the media image of health care in society. Material and method: The research was carried out using the author's questionnaire. 210 responses were collected and analyzed. Results: The study involved men (29%) and women (71%). Majority (89.52%) of respondents were in favor of an unfavorable or neutral overall image of health care created by the media. Information reached almost 70% of respondents on long queues for visits to specialists, half a year or more. The respondents (83.81%) also drew attention to references spreading in publishers about the lack of staff among medical workers. However, most people (69.52%) did not share the healthcare model shaped by the "fourth authority" based on their experience. Conclusions: Based on the analysis, a negative media impact on the healthcare picture was confirmed. The data suggests that society does not quite agree with the media image of healthcare.